Medicolegal Autopsy, Collection and Submission of Postmortem Specimens from Deceased Persons with Known or Suspected COVID-19 - Sultan, Mohammad Tipu; Islam, Md Mozaharul; Mozaffor, Miliva; Sultana, Tahmina; Sanwar, Kursiya (Mediscope, 2022)
WHO declared COVID-19 a global pandemic on 11th March, 2020. The heightened fear regarding COVID-19 is a result of many things. It is a new pathogen with some unknown characteristics, and misinformation is all over the news and social media. In this pandemic situation, to combat any known or unknown biohazard risk associated with medicolegal autopsy, handling autopsy specimens, each section of the diagnostic procedure and laboratory processes have some specific guidelines for handling infectious agents like spread of SARS-CoV-2 that convey excessive risk for exposure and possible infection and/or occupational injury. These risks typically are associated with design flaws or lack of or inadequacy of safety procedures and training. However, we still lack a concrete guideline in our country on medicolegal autopsy, collection and submission of postmortem specimens from deceased persons with known or suspected covid-19 cases during this pandemic situation. This review aims to provide some evidence-based recommendations for biosafety and infection control practices during autopsy procedures, specimen collection, handling and submission for biochemical and toxicological analysis. The guidance can be followed by coroners, forensic investigators, biochemist and pathologist as well as other workers involved in postmortem service and respective authority/department. Mediscope 2022;9(1): 41-46